Indonesia Well Abandonment Standard Gap Analysis; A Review and Suggestion - Ganesha R Darmawan (Universitas Islam Riau (UIR) Press, 2021)
The old oil and gas wells of approximately 70% are found to have no economic value in Indonesia, leading to being abandoned during the end of their lifecycle, as ruled by the government. This is part of decommissioning an entire field with an environmental preservation program, known as an Abandonment and Site Restoration (ASR). The program involves the evaluation of international permanent abandonment standards, as references for the designs, comparisons, and assessments of Indonesia’s policies. It also provides contrast gap analysis and suggestions in ensuring a proper permanent plug and abandonment approach, to avoid any future leaks or re-abandonment operations. Therefore, this study aims to determine and evaluate the gap analysis between Indonesia and International Well Abandonment Standards, as well as OGUK and NORSOK D-010. The results showed that abandonment activities had improvement opportunities philosophy, and practice, used for plugging/isolations, control lines, as well as reservoir and annular barriers. In addition, literature studies were performed to understand the abandonment philosophy for all reviewed standards, to provide proper suggestions or improvements.